The Solar Lunar Orientations of the Orkney-Cromarty and Clava Cairns - Scott, Douglas (Journal of Skyscape Archaeology, 2016)
This paper outlines the background to earlier studies of the orientation of the OrkneyCromarty (OC) passage cairns and the Clava passage and ring cairns, and details the outcome of a new and comprehensive survey carried out by the author over recent years. The paper sets out evidence of orientations in both sets of cairns to the eight divisions of the year and tests whether the alignments were observable. The results were compared to see if the Clava cairns had been influenced by the older OC cairns. Other solar and/or lunar aligned monuments are also briefly examined, as is relevant folklore.